STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM ERA DIGITALISASI DI SMP SULTAN AGUNG SEYEGAN SLEMAN YOGYAKARTA - Hidayatullah, Hidayatullah (ADDABANA: Jurnal Pendidikan Agama Islam, 2023)
Abstract: One of the negative impacts of current technological developments on the world of education is that it overrides the quality of educational content and causes students to become distracted by unimportant technological features. Even so, today's digital technology can provide access to a wider and more diverse range of educational resources. This study discusses the digitalization era Islamic Religious Education learning strategies at Sultan Agung Seyegan Middle School, Sleman, Yogyakarta. The purpose of this study is to explore the techniques and learning strategies of Islamic religious education at Sultan Agung Seyegan Middle School while still following the current era of digitalization. The method in this research is descriptive qualitative. The results of this study concluded that the process of implementing Islamic religious education learning at SMP Sultan Agung Seyegan Sleman was good, with indicators of utilization of learning resources in the form of textbooks, digital online media and companion books for students, the use of various methods including lecture methods, assignments, games, digital media, social media ; and carrying out continuous evaluations through portfolios, assignments, attitude assessments while participating in learning. Keywords: Digitalization, Islamic Religious Education, Learning Strategy. Abstrak: Salah satu dampak negatif dari perkembangan teknologi saat ini terhadap dunia pendidikan adalah mengesampingkan kualitas konten pendidikan dan menyebabkan peserta didik menjadi teralihkan oleh fitur teknologi yang tidak penting. Meski begitu, teknologi digital saat ini dapat memberikan akses sumber daya pendidikan yang lebih luas dan beragam. Penelitian ini membahas strategi pembelajaran Pendidikan Agama Islam era digitalisasi di SMP Sultan Agung Seyegan Sleman Yogyakarta. Tujuan dari penelitian ini adalah untuk mengeksplorasi teknik dan strategi pembelajaran pendidikan agama Islam di SMP Sultan Agung Seyegan dengan tetap mengikuti era digitalisasi saat ini. Metode dalam penelitian ini adalah deskriptif kualitatif. Hasil penelitian ini menyimpulkan bahwa proses pelaksanaan pembelajaran pendidikan agama Islam di SMP Sultan Agung Seyegan Sleman sudah baik, dengan indikator pemanfaatan sumber belajar berupa buku teks, media online digital dan buku pendamping bagi siswa, penggunaan berbagai metode meliputi metode ceramah, penugasan, permainan, media digital, media sosial; dan melakukan evaluasi berkelanjutan melalui portofolio, penugasan, penilaian sikap selama mengikuti pembelajaran. Kata kunci: Digitalisasi, Pendidikan Agama Islam, Strategi Pembelajaran.